Dermatological insight as the key to diagnosing intestinal Behçet’s disease misdiagnosed as Crohn’s: a case report - Caterina Mariarosaria Giorgio; Eugenia Veronica Di Brizzi; Gaetano Licata; Carmine Fiorentino; Giuseppe Argenziano; Luca Damiani (Dermatology Reports)
This report presents the case of a 22-year-old male with recurrent genital ulcers, oral aphthae, and gastrointestinal ulcerations initially diagnosed as Crohn’s disease by gastroenterologists. Despite overlapping clinical and histological features between Crohn’s disease and intestinal Behçet’s disease, a dermatological consultation raised suspicion for Behçet’s, leading to a revised diagnosis. This case highlights the helpful role of dermatologists in avoiding misdiagnosis and ensuring appropriate treatments for complex inflammatory conditions.